The relationship between curriculum and the republican ideal in the end of the 19th century: the case of the paulist school groups - RAPHAEL, Cintia Lima (2019)
This article focuses on the curriculum elaborated and addressed to the public elementary schools of the state of São Paulo, at the end of the 19th century, at the beginning of the Brazilian Republic, in the figure of school groups, and its composition based on the illuminist ideals. Republicans, sign of modernity and progress, seeking a break with the tradition of royal schools, precarious and based on the teaching of reading, writing and counting, and the figure of the schoolmaster. Thus, it is from this theme that we elaborate the reflections of this article. From this, elements such as curriculum, school groups, republican ideas and primary education were keywords taken into consideration in the search for the material to be read. Searches were performed on the following databases: Capes Thesis Bank; Scielo and Google Scholar. Books, theses and dissertations, articles in journals and works published in annals of scientific events in the area of ??Education were consulted. Based on the readings made, it was possible to make a brief analysis of the relationship between the construction and establishment of a curriculum, its cultural components and its potential regarding the break with certain traditions and the configuration or (attempt of configuration) of a new one. scenario, regarded as modern and innovative as opposed to what was sought to obliterate. Thus, it is expected to contribute with the addition of elements to the discussions on the curricular theme within the historiography of Brazilian education and, in particular, São Paulo. Submissão: 2019/02/03. Aceito em: 2019/06/20.